Molecular and Biochemical Characterization of YeeF/YezG, a Polymorphic Toxin-Immunity Protein Pair From Bacillus subtilis - Kaundal, Soni; Deep, Amar; Kaur, Gundeep; Thakur, Krishan Gopal (Frontiers in Microbiology, 2020)
Polymorphic toxins are important and widespread elements of bacterial warfare that help in restricting the growth of competitors, aid kin selection, and hence help in shaping bacterial communities. Though widespread, polymorphic toxin systems (PTS) have been extensively studied in Gram-negative bacteria, there are limited studies describing PTS in Gram-positive bacteria. The present study characterizes YeeF/YezG, a predicted member of a PF04740 family of the polymorphic toxin-immunity system from a Gram-positive bacteria Bacillus subtilis. The expression of the C-terminal toxic domain of YeeF, YeeF-CT, causes growth inhibition and gross morphological changes in Escherichia coli. The observed toxic effects are neutralized by the co-expression of yezG, a gene present downstream of yeeF, confirming YeeF-CT/YezG as a toxin/immunity protein pair. Biochemical and in vivo studies reveal that YeeF-CT causes toxicity due to its non-specific metal-dependent DNase activity, which is different from the previously reported RNase activity from the three B. subtilis toxins belonging to PF04740 family. Isothermal titration calorimetry (ITC) data analysis suggests that YeeF-CT binds YezG with a dissociation constant in the nanomolar range. Analytical ultracentrifugation studies revealed that YeeF-CT forms a homodimer and binds with two molecules of monomeric YezG immunity protein to form a 2:2 stochiometric heterotetrameric complex. Biolayer interferometry and electrophoretic mobility shift assays show that YeeF-CT/YezG/DNA forms a stable ternary complex implicating that YezG is an exosite inhibitor of YeeF-CT. This study extends the molecular targets of the toxins of the PF04740 family and hence, this family of toxins can be broadly classified as nucleases harboring either DNases or RNases activities.